Effective steel concrete structures and possibilities of their application - Kvedaras, Audronis Kazimieras; Šapalas, Antanas (Technological and Economic Development of Economy, 2004)
Application of effective building structures may induce a big economic effect in the current Lithuanian building industry. The level of strength utilization of components and materials is one of the indexes of the effectiveness of a structure. Composite steel concrete structures are composed of materials with very different mechanical properties. A brittle high‐strength centrifugal concrete core and an elastic‐plastic external shell successfully complement each other. Long‐lasting investigations in Vilnius Gediminas Technical University create a good possibility to implement such structures into real buildings. The main samples of application of composite steel concrete structures are presented in this paper.Article in Lithuanian.Efektyvios plieno betono konstrukcijos ir jų taikymo galimybėsFirst Published Online: 21 Oct 2010